GENDER DISPARITIES AND INEQUALITIES IN THE INDIAN IT SECTOR: A COMPREHENSIVE ANALYSIS - Subba, Raju; Das, Kishore Krishna (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper examines the gender status and representation in the boardrooms, management, and leadership positions, and a workforce of four major Indian IT companies: TCS, Infosys, Wipro, and HCL. The study utilizes data from the respective annual reports of the companies, focusing on the years 2018 to 2022. The results and discussion section reveal significant gender disparities and inequalities in the examined areas. In the boardrooms, women are underrepresented, with men comprising the majority of directors in all four companies. However, the chi-square test results indicate no significant evidence of gender disparity or inequality in the boardrooms. In terms of management and leadership positions, women are significantly underrepresented in all four companies. The chi-square test results confirm the presence of gender disparities and inequalities in these positions. The workforce analysis shows a substantial gender gap, with women being a minority in all four companies. The chi-square test results also reveal significant evidence of gender disparity or inequality in the workforce of these companies. The paper includes tables and figures that provide a visual representation of gender distribution and trends over the years. The representation of women in senior management positions shows some fluctuations, with TCS consistently having the highest representation. Women's representation among all employees also increases slightly over the years for most companies. Overall, the findings highlight the need for concerted efforts to address gender disparities and promote gender equality within the Indian IT sector. The study emphasizes the importance of creating inclusive and supportive environments that provide equal opportunities for women to advance and thrive in leadership positions.